Possibility of partial replacement of sodium chloride with potassium chloride and ammonium chloride in chicken ćevapčići (kebabs). Issue 1 (October 2021) - Borovic, B; Lilic, S; Milijasevic, J; Baltic, T; Jovanovic, J; Geric, T; Milijasevic, M
Abstract: The goal of this study was to investigate the influence of reducing sodium chloride content in chicken ćevapčići (kebabs) by partial replacement of sodium chloride with potassium chloride and ammonium chloride, with the target of achieving the optimal salty taste. The trial consisted of five groups. In the control group of chicken ćevapčići, only sodium chloride was added. In group 1, one third of sodium chloride was replaced with potassium chloride; in group 2 one half of the sodium chloride was replaced with potassium chloride; in group 3, one third of sodium chloride was replaced with ammonium chloride. In group 4, sodium chloride was half reduced and one quarter of ammonium chloride in the relation to control group was added. Sensory evaluation was performed by ten trained assessors using numeric scales. Evaluations of colour acceptability and consistency showed there were no statistical differences (P>0.05) between the ćevapčići. The most expressed saltiness was evaluated in the control ćevapčići group due to it having the largest amount of added sodium chloride, as well in group 3 ćevapčići, wherein one third of the sodium chloride was replaced with ammonium chloride.